Supporting College Student Success through Applied Learning: Considering Associations with Average College Grades, Graduation in Four Years, and Degree Aspirations - Elizabeth Jach; Teniell Trolian (Journal of Postsecondary Student Success, 2023)
While previous research has examined the association between various forms of applied learning and effects on student outcomes, the present study examines engagement in forms of applied learning and three distinct measures of student success. Using longitudinal data from the Wabash National Study, this analysis examined the relationship between undergraduate participation in forms of applied learning and students’ graduation within four years, fourth-year college grades, and post-baccalaureate degree aspirations. Results suggested that certain applied learning experiences were associated with specific forms of student success. Specifically, the odds of graduation within four years increased for students who participated in internship, capstone, or study abroad experiences but decreased for students who participated in an independent study or volunteer experience. Applied learning experiences associated with higher college grades included faculty asking students to apply theories or concepts to practical problems or in new situations, completing an independent study, capstone, internship, research with a faculty member, or study abroad experience, but applying concepts to exams or assignments was associated with lower college grades. Finally, higher levels of students’ educational aspirations were associated with participating in research with a faculty member and study abroad. Together, these findings emphasize the need for institutions of higher education, faculty, and student affairs practitioners to nuance applied learning opportunities in relation to student success goals.